Pyocyanin derived from the marine sponge-associated bacterium, Pseudomonas aeruginosa P1.S9, has the potential as antibacterial - DOVA KELVIN MESRIAN; RIKA INDRI ASTUTI; MUHAMMAD EKA PRASTYA; ARIS TRI WAHYUDI (Society for Indonesian Biodiversity, 2024)
Abstract. Mesrian DK, Astuti RI, Prastya ME, Wahyudi AT. 2024. Pyocyanin derived from the marine sponge-associated bacterium, Pseudomonas aeruginosa P1.S9, has the potential as antibacterial. Biodiversitas 25: 4139-4147. Sponge-associated bacteria are a prolific source of secondary metabolites. Among them, pyocyanin-producing Pseudomonas aeruginosa is a subject of great interest. Pyocyanin is a blue-green pigment known for its enormous biological activity, one of the most notable being antimicrobial. Therefore, this study was performed to optimize the production, to characterize the chemical structure, and to test the antimicrobial activity of pyocyanin. As the sole isolate used, Pseudomonas aeruginosa P1.S9 provided a fundamental premise for pyocyanin synthesis by revealing the presence of phzM and phzS genes. The proteins generated from these genes were highly compatible with two enzymes involved in the pyocyanin production pathway. During the optimization, the maximum level of pyocyanin produced was 29.057±0.691 µg mL-1. The concentration was obtained using a modified King's A medium incubated at 27°C within four days. To assess its purity, the chemical structure of pyocyanin was confirmed by several spectroscopic techniques including UV-Visible (UV-Vis), Fourier Transform Infrared (FT-IR), and Nuclear Magnetic Resonance (1HNMR). All test results closely resemble purified pyocyanin compared to several prior studies. In terms of antimicrobial activity, pyocyanin was effective against ATCC strains of Bacillus subtilis, Escherichia coli, Pseudomonas aeruginosa, and Staphylococcus aureus. Its strongest minimum inhibitory concentration (MIC) was 62.5 µg mL-1 against Bacillus subtilis. Subsequently, the accumulation of reactive oxygen species (ROS) as a major mechanism of pyocyanin antibacterial activity has also been verified. The bacterial pathogens cells treated with pyocyanin displayed a brighter luminescence compared to the control without pyocyanin after the addition of 2',7'-dichlorodihydrofluorescein diacetate (H2DCF-DA). Ultimately, the present work comprehensively characterized pyocyanin's promising producer and antibacterial properties.